Aktivitas antioksidan tepung labu kuning dari berbagai varietas dengan variasi suhu pengeringan - Akhmad Mustofa; Nanik Suhartatik; Dwi Yulia Vina Pratiwi (Agroindustrial Technology, University of Trunojoyo Madura, 2024)
Pumpkin is an annual plant that is widely available in Indonesia. Pumpkin will quickly spoil and rot if the hard skin is injured. Pumpkin is a type of food that contains high antioxidant activity. To prevent damage to pumpkin, this fruit can be processed into flour. The purpose of this study was to determine the varieties of pumpkin and the most optimal drying temperature to produce pumpkin flour which has the highest antioxidant activity. The study was conducted using a factorial Completely Randomized Design (CRD) consisting of 2 factors. The first factor is the yellow pumpkin varieties, namely machete pumpkin, kabocha pumpkin, and honey pumpkin while the second factor is the drying temperature at 50 ℃, 60 ℃, and 70 ℃ with a drying time of 11 hours. The result showed that Kabocha pumpkin varieties and drying temperature of 60 ℃ produced pumpkin flour with the highest antioxidant activity of 88.05 %. Other chemical characteristics of this pumpkin flour are water content of 13.30 %, beta-carotene 0.16 g/g, total phenol 23.81 mg gallic acid equivalent/g, total sugar 23.55 %, and yield of 10.94 %.